Green HRM: Goal Attainment through Environmental Sustainability - Uddin, Mohammad Main; Islam, Rabiul (Journal of Nepalese Business Studies, 2016)
The green Human Resources Management has emerged from companies engaging in practices related to protection of environment and maintaining ecological balance. The slogan is earning profit through environmental sustainability. This paper proposes the development of a model of green human resource management by reviewing the literature on human resource aspects of environmental management. The study followed archival method of literature review. The literature has been classified on the basis of entry to exit processes in the HRM on the basis of available literature on green Human Resources. From the perspective of green human resource management, this study argues that Green HRM can play a useful role in business in promoting environment related issues by adopting and following the processes. Finally, the paper proposes some research agenda for the future study. Journal of Nepalese Bussiness Studies Vol. 9, No. 1, 2015 pp. 13-19